1979
DOI: 10.1161/01.cir.60.6.1300
|View full text |Cite
|
Sign up to set email alerts
|

Exercise cross-sectional echocardiography in ischemic heart disease.

Abstract: SUMMARY We performed cross-sectional echocardiograms at rest, during supine bicycle exercise, and after sublingual nitroglycerin administration in 28 patients suspected of having ischemic heart disease. Technically adequate exercise cross-sectional echocardiograms were obtained in 20 patients (71%). Ten patients had new areas of reversible segmental dysynergy, and all 10 had significant stenoses of coronary arteries supplying areas of the heart corresponding to the location of reversible dysynergy. Six of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
4

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(56 citation statements)
references
References 30 publications
1
50
0
4
Order By: Relevance
“…This is similar to the 75% to 90% rate of acceptable studies obtained by other authors. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] When the criteria of percentage change in peak ejection velocity of less than 85% or an absolute value for peak ejection velocity of 1.1 m/sec at maximal exercise is used, subjects with normal left ventricular function may be differentiated from patients with significant coronary artery disease and ischemic left ventricular dysfuntion. Further study is necessary to evaluate the changes in peak ejection velocity in patients with congestive cardiomyopathy and those with left ventricular dysfunction at rest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the 75% to 90% rate of acceptable studies obtained by other authors. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] When the criteria of percentage change in peak ejection velocity of less than 85% or an absolute value for peak ejection velocity of 1.1 m/sec at maximal exercise is used, subjects with normal left ventricular function may be differentiated from patients with significant coronary artery disease and ischemic left ventricular dysfuntion. Further study is necessary to evaluate the changes in peak ejection velocity in patients with congestive cardiomyopathy and those with left ventricular dysfunction at rest.…”
Section: Discussionmentioning
confidence: 99%
“…2, 413-419, 1987. RECENT STUDIES have shown that pulsed Doppler velocity measurements can accurately estimate stroke volume and cardiac output at rest. [1][2][3][4][5] In addition, the technique is reported to reflect changes in blood flow during exercise in normal subjects.`However, little data are available that assess the Doppler-derived variables of aortic flow during exercise in patients with coronary artery disease.9'-Two-dimensional echocardiography has been shown to increase the sensitivity of exercise testing in the detection of coronary artery disease when used either during [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] or immediately after exercise18-20 by demonstrating the percent changes in both global and segmental left ventricular function.…”
mentioning
confidence: 99%
“…In the last 35 years, since one of the first descriptions of twodimensional stress echocardiography (2D-SE) by Wann et al (44), 2D-SE has considerably developed. This method is cost effective, safe and free of non-ionizing radiation (32).…”
Section: Sementioning
confidence: 99%
“…24 Ancak, özellikle hiperpne nedeni ile yeterli ekokardiyografi görüntü-sünün alınamaması bu testi teknik olarak zorlaştır-mıştır. Son yıllarda geliştirilen stres ekokardiyografi bu kısıtlamaları ortadan kaldırmıştır.…”
Section: Sonuçunclassified